Evaluating the accuracy of the regularized and tension spline interpolation methods to estimate and map the concentration of nitrate on the surface water of Pulau Tuba, Langkawi, Kedah / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Lee Mohd Affindi, Behzad Khairiah; Ramli, Noordalila; Mohd Tahir, Jumiati; Zainal, Nurrul Zulaikha; Ahmad Afiza, Syasya Adhwa; Abd.Aziz, Khairul Naim; Roslani, Muhammad Akmal; Zainol, Zamzila Erdawati; Ahmad, Aziani; Shaari, Mohd Idrus; Ramli, Rohayu; et al. (UiTM Cawangan Negeri Sembilan, 2022)
This study aims to evaluate the efficiency of the regularized and tension spline interpolation methods to predict and map nitrate concentration on the surface water of Pulau Tuba, Langkawi. Kedah. Sampling activities were carried out using the Niskin Water Sampler and immediately brought into the lab to determine the nitrate level using an Ultraviolet Visible spectrophotometer and the cadmium reduction method. The geolocations of sampling points were recorded using the Geographic Positioning System (GPS). The training set (50%) and the testing set (50%) were chosen randomly based on 20 sampling points. Two types of spline interpolation methods were compared: the regularized and tension spline interpolation methods. Evaluation of prediction of models was carried out using the correlation analyses, linear regression analysis and error analyses when comparing the actual and prediction values. Determination of the map accuracy was carried out after inserting map elements. The study found that the tension spline method had a better prediction of nitrate concentration. The accuracy of the map was found to be at 90%. The study's outcome can be used as guidelines by concerned parties to monitor, manage, and develop strategic policies for the sustainable development of the coastal water of Pulau Tuba, Langkawi, Kedah.